Workshop Penulisan Artikel Ilmiah Populer bagi Guru SMA Negeri 9 Purworejo - Setiyono, Junaedi; Rokhayati, Titi; Setyawati, Vita Rahayu (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The problems faced by teachers at SMA Negeri 9 Purworejo are the lack of understanding of popular scientific article writing techniques and the lack of knowledge about obtaining ideas or concepts to be used as a thesis. The Community Service Activity of Muhammadiyah University of Purworejo in collaboration with SMA Negeri 9 Purworejo aims to facilitate teachers in understanding popular scientific article writing techniques and knowledge about obtaining ideas or concepts to be used as a thesis. The method used is a lecture followed by questions and answers and writing practice. The lecture material is mainly in the form of popular scientific article writing techniques. The competence to write popular scientific articles is useful for teachers, especially to meet the requirements for promotion. In addition, teachers have the opportunity to share knowledge not only in class or at school but also with the wider community. This community service activity is a trigger for motivation for teachers to write down their ideas or concepts before being refined into popular scientific articles. The writings of the teachers in the form of theses which are the most important part of popular scientific articles are appreciated by the resource persons by discussing their advantages and how to improve their shortcomings. By discussing the thesis in the form of sentences, writings and the enthusiasm of the teachers that appeared in the question and answer session, workshop activities containing material presentations by resource persons followed by questions and answers and the practice of writing popular scientific articles. By appreciating and discussing the theses written by these teachers, more or less, it has been able to overcome the problems faced by most teachers regarding the lack of understanding of the techniques for writing popular scientific articles and the lack of knowledge about obtaining ideas or concepts to be used as the thesis for writing